Identitas Jawara Banten Tak Lekang Dimakan Zaman di Era Globalisasi dan Modernisasi ( Studi Kasus Jawara di Desa Terumbu, Kec. Kasemen Kota Serang ) - Suherman Arifin; April Laksana; Irwanto Irwanto; Mohamad Ikrom Arasid (Journal on Education, 2023)
One of the timeless cultural heritages is the designation of the word jawara. The purpose of study is to analyze the context of a champion in the era of globalization and modernization whose existence is still recognized, mainly related to someone who has martial arts skill or is also called a martial arts expert. Interaction theory by Pierre Felix Bourdiou is used in this study and interprets the term champion to describe martial arts experts either to protect themselves or to defend the weak as a result of oppression by the authorities. Qualitative description is a tool for analyzing this research either from the direct recognition of the winner in the currentsituation or the events and actions of the champion in the past. Using several analyzes, namely interviews with several martial arts figures, description of whereabouts and the image of the current champion. The existence of a champion in the midst of society communication events and communication actions. This study concludes that the existence of the jawara was formed when the sultanace of banten was founded which continued until the dutch colonial era, the dutch even labeled the jawara as a bandit who disrupted security and was labeled negatively because he was synonymous with acts of violence and deviated from dutch colonial law. The term jawara is a cultural subculture of the Indonesia nation and is a means of communicating nasional identity